Transfers and development: Easy come, easy go? - Luc Christiaensen; Lei Pan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Contrary to the popular notion that money that is easily earned, is also easily spent, economic theory holds that income is fungible. Drawing on the concept of mental accounting, this study theoretically explores when such a link between spending behaviour and the effort dispensed in obtaining income is plausible. Empirically, it is found that the marginal propensity to consume from unearned income is about three times larger than that from earned income, based on household panel data from rural China, with the difference more pronounced when unearned income is transitory and smaller than earned income. The policy implications are real.
Keywords: D01; D11; D12; O12; 330; transfers; saving; mental accounting; permanent income hypothesis; China; Einkommenshypothese; Verbraucherausgaben; China